Morphological Characterization of Eutectic Si and Ge Phases in the Corresponding Al-15Si and Al-20Ge Alloys Using FIB Tomography - N. Wanderka; H. Kropf; M. Timpel (Jordan Journal of Physics, 2025)
The three-dimensional morphology of the eutectic Ge phase in samples modified by Ca and Y in the hypoeutectic Al-20Ge alloy has been investigated by focused ion beam tomography. Addition of Ca (0.2 wt.%) caused a modification of the eutectic Ge phase from a branched plate-like morphology to a compressed cylinder-like shape of smaller dimensions. Addition of Y (0.2 wt.%) resulted in a transformation of the eutectic Ge phase with two types of morphology. One type is vermicular-like in 2D and refined plate-like in 3D, while the other appears as a holey Ge matrix with an embedded eutectic Al phase of rod-like morphology. The morphology of the modified eutectic Ge has been discussed in terms of possible growth mechanisms compared with that of the as-cast non-modified Al-20Ge alloy and that of well-known Sr-modified eutectic Si in Al-Si system. Keywords: Hypoeutectic Al-Ge alloys, Modification of eutectic Ge phase, Focused ion beam tomography, Scanning electron microscopy .